Multifunctional liposomes interact with Abeta in human biological fluids: Therapeutic implications for Alzheimer's disease. (September 2017) - Conti, Elisa; Gregori, Maria; Radice, Isabella; Da Re, Fulvio; Grana, Denise; Re, Francesca; Salvati, Elisa; Masserini, Massimo; Ferrarese, Carlo; Zoia, Chiara Paola; Tremolizzo, Lucio
Abstract: The accumulation of extracellular amyloid beta (Abeta42) both in brain and in cerebral vessels characterizes Alzheimer's disease (AD) pathogenesis. Recently, the possibility to functionalize nanoparticles (NPs) surface with Abeta42 binding molecules, making them suitable tools for reducing Abeta42 burden has been shown effective in models of AD. Aim of this work consisted in proving that NPs might be effective in sequestering Abeta42 in biological fluids, such as CSF and plasma. This demonstration is extremely important considering that these Abeta42 pools are in continuum with the brain parenchyma with drainage of Abeta from interstitial brain tissue to blood vessel and plasma. In this work, liposomes (LIP) were functionalized as previously shown in order to promote high-affinity Abeta binding, i.e., either with, phosphatidic acid (PA), or a modified Apolipoprotein E-derived peptide (mApo), or with a curcumin derivative (TREG); Abeta42 levels were determined by ELISA in CSF and plasma samples. mApo-PA-LIP (25 and 250 μM) mildly albeit significantly sequestered Abeta42 proteins in CSF samples obtained from healthy subjects (p < 0.01). Analogously a significant binding (∼20%) of Abeta42 (p < 0.001) was demonstrated following exposure to all functionalized liposomes in plasma samples obtained from selected AD or Down's syndrome patients expressing high levels of Abeta42. The same results were obtained by quantifying Abeta42 content after removal of liposome-bound Abeta by using gel filtration chromatography or ultracentrifugation on a discontinuous sucrose density gradient. In conclusion, we demonstrate that functionalized liposomes significantly sequester Abeta42 in human biological fluids. These data may be critical for future in vivo administration tests using NPs for promoting sink effect. Highlights: The use of high affinity Abeta binding liposomes is proposed in human biological fluids. Functionalized liposomes significantly interact with Abeta in plasma and CSF from AD patients. Liposomes may exploit the Abeta "sink effect" as a potential therapeutic strategy.